A cost-benefit analysis of the EU 20/20/2020 package - Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
The European Commission did not publish a cost-benefit analysis for its 2020 climate package. This paper fills that gap, comparing the marginal costs and benefits of greenhouse gas emission reduction. The uncertainty about the marginal costs of climate change is large and skewed, and estimates partly reflect ethical choices (e.g., the discount rate). The 2010 carbon price in the ETS can readily be justified by a cost-benefit analysis. Emission reduction is not expensive provided that policy is well-designed, a condition not met by planned EU policy. It is probably twice as expensive as needed, costing one in ten years of economic growth. The EU targets for 2020 are unlikely to meet the benefit-cost test. For a standard discount rate, the benefit-cost ratio is rather poor (1/30). Only a very low discount rate would justify the 20% emission reduction target for 2020.
Keywords: 330; European Union; climate policy; cost-benefit analysis